Bone morphogenetic protein 2 stimulates chondrogenesis of equine synovial membrane-derived progenitor cells - Chen, Yuwen; Caporali, Evelyn; Stewart, Matthew (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objectives: Bone morphogenetic protein 2 (BMP-2) is critical for skeletal and cartilage development, homeostasis and repair. This study was conducted to clone and characterize equine BMP-2, develop expression constructs for equine BMP-2, and to determine whether BMP-2 can stimulate chondrogenesis of equine synovial membrane-derived progenitor cells (SMPC).Methods: Equine BMP-2 cDNA was amplified from chondrocyte RNA, and then transferred into an expression plasmid and adenoviral vector. Effective expression of equine BMP-2 was confirmed using a BMP reporter cell line. SMPC were isolated from synovium, expanded through two passages and transferred to chondrogenic cultures, with recombinant human (rh) transforming growth factor beta 1 (TGF-[uni03B2]1) or rhBMP-2. Chondro-genesis was assessed by up-regulation of collagen types II and X, and aggrecan mRNA, secretion of collagen type II protein and sulfated glycosaminoglycans (sGAG), and by alkaline phosphatase induction. Chondrogenic stimulation of SMPC by the equine BMP-2 adenovirus was assessed by sGAG secretion and histology.Results: The mature equine BMP-2 peptide is identical to human and murine peptides. Recombinant human BMP-2 and TGF-[uni03B2]1 stimulated equivalent amounts of collagen type II protein in SMPC pellets, but sGAG secretion was doubled by BMP-2. Neither factor stimulated hypertrophic marker expression. The equine BMP-2 adenoviral vector induced chondrogenesis comparably to rhBMP-2 protein, with no indication of hypertrophy.Clinical significance: Bone morphogenetic protein 2 is a potent inducer of SMPC nonhypertrophic chondrogenesis, supporting the use of this combination for articular cartilage repair applications.
Keywords: Equine BMP-2; bone morphogenetic protein 2; synovial membrane progenitor; chondro-genesis; adenoviral vector